Credit utilisation among rice farmers in Oyo state, Nigeria (2010)
Assessment has to be made: (ii) assessment of a bank's performance involves both quantitative and qualitative factors; (iii) there is the problem of identifying banks' inputs and outputs; and (iv) the existence of several heterogeneous ,inputs and outputs. That cannot be easily compared. The study makes use of Data Envelopment Analysis in an attempt to measure the relative efficiency of commercial banks. It was observed that inefficiencies link more to inefficient resource utilisation rather than production scale. Also, Nigerian Banks were noted to be highly operationally inefficient. Hence, it is not sufficient to increase the capital base but it is important to make the environment more competitive, and to improve the absolute efficiency of the industry.